Peran Dan Model Strategi Komunikasi Asosiasi Provinsi (Asprov) Pssi Jawa Tengah Dalam Menyelenggarakan Kompetisi Sepakbola Liga 3 Jawa Tengah 2023 - Ulinnuha, Muhammad; Nurrachmad, Limpad (Innovative: Journal Of Social Science Research, 2024)
The 2023 Central Java League 3 Competition is a work program of PSSI Central Java in carrying out its duties as a Central Java football organization. Communication is needed for the smooth running of the competition so that all clubs and the community can follow the development of the competition properly. The research uses qualitative descriptive with observation data collection techniques, interviews, and documentation with validity checked through triangulation of sources and data. Data validity through triangulation of data collection techniques, and data analysis techniques involves data reduction, data presentation, and data verification. The results of the study show that the Central Java PSSI Asprov implements the communication strategy model according to Hafield Cangara, including the stages of communication research, communication planning, communication implementation, measurement or evaluation, and competition reporting. However, there are obstacles in carrying out this communication. The conclusion of the research on the communication strategy of the Central Java PSSI Asprov uses a communication strategy model in accordance with the communication strategy theory by Hafield Cangara, namely research, planning, execute, measure or evaluation, and report.